Disentangling the Minimum Wage Puzzle: An Analysis of Worker Accessions and Separations - Pedro Portugal; Ana Rute Cardoso (Institute for the Study of Labor (IZA), 2002)
Changes in the legislation in the mid-80s in Portugal provide remarkably good conditions for analysis of the employment effects of mandatory minimum wages, as the minimum wage increased sharply for a very specific group of workers. Relying on a matched employer employee panel data set, we model gross worker flows – accessions and separations – in continuing firms, as well as in new firms and those going out of business, using a count regression model applied to proportions. Employment trends for teenagers, the affected group, are contrasted to those of older workers, before and after the raise in the youth minimum wage. The major effect on teenagers of a rising minimum wage is the reduction of separations from the employer, which compensates for the reduction of accessions to new and continuing firms. In this sense, our results can reconcile some of the previous evidence that has been presented in the empirical literature when analyzing the aggregate impact of the minimum wage on youth employment without decomposing it by type of worker flow.
Keywords: J23; D21; J38; 330; minimum wage; employment; Mindestlohn; Arbeitsmobilität; Schätzung; Portugal